Microstructural characterization and mechanical properties of (TiB + TiC) reinforced Ti–6Al–4V prepared by melt hydrogenation - Botao Jiang; Liang Wang; Hui Yan; Jiliang Teng; Binbin Wang; Liangshun Luo; Ruirun Chen; Yanqing Su; Jingjie Guo; Hengzhi Fu (Journal of Materials Research and Technology, 2023)
TiB and TiC reinforced Ti–6Al–4V matrix composites were prepared by melt hydrogenation, in which the total fraction of the reinforcements was 5 vol % and the ratio of TiB to TiC was 1:1. The effects of melt hydrogenation on the solidification process, phase composition, and microstructure of the titanium matrix were studied. The morphology and distribution of the reinforcement without and with hydrogen were observed. Moreover, the nano-hardness of the composites was measured. The results show that the solidification process of the matrix can be changed by melt hydrogenation, which resulting the increase of β phase and refining of α lamellar in titanium alloy. Hydrogen increased the size of the reinforcements, which aggregated at the grain boundary of the primary β phase and formed a network structure. Hydrogen reduced the nano-hardness both of the titanium alloy and the reinforcements slightly. In summary, melt hydrogenation can maintain or slightly reduce the strength of the composites at room temperature and decrease the nano-hardness.